Poverty Alleviation Efforts During the Covid Period 19 in Indonesia (a Study of Maudhu'i Interpretation) - Abu Sahman Nasim; Hasyim Haddade (Formosa Journal of Sustainable Research, 2023)
This study aims to analyze efforts to reduce poverty during the Covid-19 period in Indonesia (A Maudhu'i Tafsir Study). It also aims to look deeper into the implementation of poverty reduction in the maudhu'i interpretation approach with general and specific arguments. This research uses descriptive qualitative. Data is collected through interviews, observation, and documentation. This study uses data analysis techniques which consist of the stages of data collection, data reduction, data presentation, and drawing conclusions. The results of the study show that ways of alleviating poverty in Islam and the Indonesian government can affect poverty reduction with an approach based on Juridical-Empirical studies. Part of the reinforcement is to anticipate various poverty problems during the Covid-19 era which seem to threaten the people's economy in Indonesia. however, in a society whose structure and organization is simple, poverty may not be a social problem, because they think that everything is predestined, so there are no efforts to overcome it. Therefore, poverty alleviation efforts are needed during the Covid-19 period in Indonesia by using an approach in Islam as a massive and structured effort in the success of the Republic of Indonesia's government programs